Nitric Oxide and Hydrogen Sulfide: A Nice Pair in the Respiratory System - Fuschillo, Salvatore; Palomba, Letizia; Capparelli, Rosanna; Motta, Andrea; Maniscalco, Mauro (Current Medicinal Chemistry, 2020)
Nitric Oxide (NO) is internationally regarded as a signal molecule involved in several functions in the respiratory tract under physiological and pathogenic conditions. Hydrogen Sulfide (H2S) has also recently been recognized as a new gasotransmitter with a diverse range of functions similar to those of NO. Depending on their respective concentrations, both these molecules act synergistically or antagonistically as signals or damage promoters. Nevertheless, available evidence shows that the complex biological connections between NO and H2S involve multiple pathways and depend on the site of action in the respiratory tract, as well as on experimental conditions. This review will provide an update on these two gasotransmitters in physiological and pathological processes.
Keywords: outcome